In vitro replication of bacteriophage phi 29 DNA. - Watabe, K (1982)
We have been studying the mechanisms of linear DNA replication by using Bacillus bacteriophage phi 29 as a model system. To isolate and characterize the proteins required for phi 29 DNA replication, we have developed a cell-free replication system. A cell-free extract prepared from phi 29-infected Bacillus subtilis catalyzes the semiconservative replication of phi 29 DNA, but only if exogenous phi 29 DNA-protein complex is used as the template. This template consists of linear duplex DNA with a 30,000-dalton terminal protein attached covalently to both 5' ends. Replication starts nonsimultaneously at or near both ends of the template. The extract also catalyzes the specific binding between dATP and the phi 29 terminal protein. Thus, the in vitro system closely mimics the in vivo replication of phi 29 DNA. This system should allow characterization of the phi 29 DNA replication machinery.